Objects in motion in the early modern world - Bleichmar, Daniela 1973-; Martin, Meredith (Meredith S.) (Art history book series, 2016)
"Objects in motion in the early modern world presents a collection of twelve original essays that examine the circulation of objects across a variety of global regions and cultures from the sixteenth to eighteenth centuries that reveal the importance of mobility for understanding the production, use, and meanings of early modern art. Individual essays trace the routes of an unusually wide range of cultural, geographical, and material examples -- including Persian silk textiles in Venice, Chinese porcelain along the Swahili Coast, exotic South Pacific bird specimens in Holland, and various European objects through India and Siam. The multiple mechanisms by which each of these objects were transported, translated, resisted, and consumed in the early modern period are carefully explored, as well as the various forms of mobility -- both physical and interpretive -- that each historical object experienced during this period. Collectively, essays reveal how mobility provides a vital means to reconsider traditional geographies and hierarchies associated with global exchange, particularly those that privilege Western Europe. Timely and provocative, objects in motion in the early modern world sheds important new light on the mobility of objects and cultural meaning in the early modern world -- and paves the way to a consideration of broader questions about art history and its disciplinary boundaries." -- Provided by publisher